(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article examines the linguocultural characteristics of riddles formed on the basis of the lexeme rain. As a significant natural phenomenon, rain occupies an important place in the linguistic worldview of many nations and is reflected in folklore genres, particularly riddles. The study analyzes the semantic, symbolic, cultural, and cognitive aspects of rain-related riddles and reveals their role in preserving national traditions, beliefs, and values. The research demonstrates that riddles based on the lexeme rain embody both universal and culture-specific perceptions of nature.